Sustainable Business Model Components For The Islamic Banking Industry - Mohammad, Norbihan (2022)
This study investigates the current business models supporting sustainability in Islamic banks, develop the sustainable business model components that could contribute to the sustainability of Islamic banks and test customer's purchase intention for the sustainable business model components. This research focuses on Malaysia's Islamic banking business.